Effect of cadmium administration on the antioxidant system and neuronal death in the hippocampus of rats. Issue 9 (23rd June 2022) - Treviño, Samuel; Pulido, Guadalupe; Fuentes, Estefania; Handal‐Silva, Anabella; Moreno‐Rodríguez, Albino; Venegas, Berenice; Flores, Gonzalo; Guevara, Jorge; Díaz, Alfonso
Abstract: Cadmium (Cd) is a heavy metal classified as a carcinogen whose exposure could affect the function of the central nervous system. Studies suggest that Cd modifies neuronal morphology in the hippocampus and affects cognitive tasks. The oxidative stress pathway is proposed as a mechanism of toxicity. However, this mechanism is not precise yet. This study aimed to evaluate the effect of Cd administration on oxidative stress markers in the male rat's hippocampus. Male Wistar rats were divided into (1) control (drinking water) and (2) treatment with Cd (32.5 ppm of cadmium chloride (CdCl2 ) in water). The Cd was administered for 2, 3, and 4 months. The results show that the oral administration of CdCl2 increased the concentration of Cd in plasma and hippocampus, and this response is time‐dependent on its administration. Likewise, it caused an increase in lipid peroxidation and nitrosative stress markers. Moreover, it increased reactive astrogliosis and antioxidant enzyme activity. Consequently, the progression of the oxidative response exacerbated neurodegeneration in hippocampal cells. Our results suggest that Cd exposure induces a severe oxidative response that contributes critically to hippocampal neurodegeneration. It is suggested that exposure to Cd increases the risk of developing neurological diseases, which contributes to a decrease in the quality of life of the human and the environment in which it lives. Graphical Abstract: Cadmium induces oxidative/nitrosative stress that in the long term causes a chronic inflammatory and neurodegenerative process in the rat hippocampus.